Opening the Gap: Rare Lichens With Rare Cyanobionts – Unexpected Cyanobiont Diversity in Cyanobacterial Lichens of the Order Lichinales - Jung, Patrick; Brust, Katharina; Schultz, Matthias; Büdel, Burkhard; Donner, Antje; Lakatos, Michael (Frontiers in Microbiology, 2021)
The last decades of research led to a change in understanding of lichens that are now seen as self-sustaining micro-ecosystems, harbouring diverse microbial organisms in tight but yet not fully understood relationships. Among the diverse interdependencies, the relationship between the myco- and photobiont is the most crucial, determining shape and ecophysiological properties of the symbiotic consortium. Roughly 10 % of lichens associate with cyanobacteria as their primary photobiont termed cyanolichens. Up to now the diversity of cyanobionts of bipartite lichens resolved by modern phylogenetic approaches is restricted to filamentous and heterocytous genera of the order Nostocales. Unicellular photobionts were placed in the orders Chroococcales, Pleurocapsales and Chroococcidiopsidales. However, especially phylogeny and taxonomy of the Chroococcidiopsidales genera remained rather unclear. Here we present new data on the identity and phylogeny of photobionts from cyanolichens of the genera Gonohymenia, Lichinella, Peccania and Peltula from a broad geographical range. The polyphasic approach was used, combining morphological, cultivation depending characteristics (microscopy, staining techniques, life cycle observation, baeocyte motility and nitrogen fixation test) with phylogenetic analyses of the 16S rRNA and 16S–23S ITS gene region. We found an unexpected high cyanobiont diversity in the cyanobacterial lichens of the order Lichinales including two new genera and seven new species, all of which were not previously perceived as lichen symbionts. As a result we describe the novel unicellular Chroococcidiopsidales genera Pseudocyanosarcina gen. nov. with the species P. phycocyania sp. nov. (from Peltula clavata, Australia) and Compactococcus gen. nov. with the species C. sarcinoides sp. nov. (from Gonohymenia sp., Australia) and the new Chroococcidiopsidales species Aliterella compacta sp. nov. (from Peltula clavata, Australia), A. gigantea sp. nov. (from Peltula capensis; Republic South Africa), Sinocapsa ellipsoidea sp. nov. (from Peccania cerebriformis, Austria), as well as the two new Nostocales species Komarekiella gloeocapsoidea sp. nov. (from Gonohymenia sp., Czech Republic) and K. globosa sp. nov. (from Lichinella cribellifera, Canary Islands, Spain). Our study highlights the role of cyanolichens acting as a key in untangling cyanobacterial taxonomy and diversity. With this study, we hope to stimulate further research on photobionts, especially of rare cyanolichens.